The Effects of Authoritative Parenting on Career Exploration: A Mediation Analysis of Career Decision Self-Efficacy - Khoeriyah, Asri; Sunawan, Sunawan; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Career exploration is important for students to build greater awareness of the kinds of career information. This study aimed to identify and analyze the impact of authoritative parenting on career exploration mediated by career decision making self-efficacy and analyzed Vocational High School students (SMK Negeri) in Tasikmalaya City As many as 370 students of class X, XI, and XII chosen using a cluster random sampling technique. Their data were collected using parental authority questionnaire, career exploration survey, career decision self-efficacy (short form) instruments. Findings indicated a positive relationship between authoritative parenting and career exploration mediated by career decision self-efficacy. Seeing the mediating effects of career decision self-efficacy on authoritative parenting and career exploration, it can be concluded that there is a partial mediation. Further implications of this study are presented in the discussion chapter.